Geothermal refraction problem for a 2-D body of polygonal cross-section buried in the two-layered earth - HVOŽDARA, Milan; MAJCIN, Dušan (Contributions to Geophysics and Geodesy, 2009)
We present the exact boundary integral formulae for calculation of the geothermal anomaly due to a two dimensional body whose thermal conductivity is λT and its cross-section is bounded by the closed general polygonal contour. This body is buried in the superﬁcial layer of conductivity λ1 . The half-space z > h with the thermal conductivity λ2 is considered as a substratum of models. The boundary integral technique for the solution of this problem requires the application of logarithmic potential terms in inﬁnite series. Numerical calculations based on derived formulae revealed that the surface anomaly heat ﬂow reﬂects the “topography” mainly of the upper boundary of the perturbing body. The derived algorithm and the developed numerical program enable calculations for a number of interesting models: intrusions, protrusions of the substratum etc.